STRATEGI PEMASARAN JASA HOTEL SINABUNG BERASTAGI - Conie Nopinda Br Sitepu (JURNAL REGIONOMIC, 2020)
This research was conducted at Sinabung Berastagi Hotel, located in Kolam Renang Street, 1 Gundaling, Berastagi District, Karo Regency, North Sumatera, 22156. This research aims to find out and to analyze the SWOT Marketing Strategy Services in Sinabung Berastagi Hotel appropriately. In this research the sample used is Random Sampling, a Random Sampling Technique. The respondents were 45 employees. The type of research used is descriptive qualitative research. Descriptive qualitative research is a research that is described in words according to the opinion of the respondent, transparently, in accordance with the question of the researcher, and from the answers will be analyzed and concluded through SWOT Analysis. The results of the research that have been done show that the results of the IFAS matrix has an amount of 3.02 and the EFAS matrix has an amount of 2.70, the strategy used is already good because the parameter of grading 4.00 (very important) up to 1.00 (not important). However, Sinabung Beratagi Hotel still has shortcomings that must be corrected by using an aggressive strategy by maintaining existing the strengths and oppurtunities and using SO and WO strategies so that the company can run well and has progress.